Mathematical Problem-Solving Strategies Junior High School Students - Ahsan, Nurul Huda; Hartoyo, Agung; Halini, Halini (STKIP Singkawang, 2023)
This descriptive qualitative research was conducted to describe the problem-solving strategies of junior high school students on Pythagorean theorem material. The source of the research data was 23 students of class IX SMP Pontianak in the academic year 2022/2023. From this research, it is known that the variety of strategies in solving mathematics problems are trial and error, making illustrations of pictures or diagrams, trying simpler problems, making tables, finding patterns, working backward, considering several possibilities, and simplifying problems. The strategies that were widely used were trial and error (38.04%), making pictures or diagrams (17.39%), finding patterns (27.17%), and working backward (15.22%). Generally, subjects were able to understand the problem by finding the known and questionable information in the problem, only a few had difficulty formulating the problem. Similar cases were also identified when planning problem-solving strategies, most students were able to construct mathematical models and formulate problems, although there were also those who did not do this stage. In other variations, some students made illustrations of pictures or diagrams, found patterns, and worked backward. An important finding of this study is that subjects have a deep understanding of mathematical problems, and the ability to plan strategies and apply them appropriately affects students' success in solving problems.